Логіка юридичних міркувань - Тягло, О. В.; Tiaglo, O. V.; ORCID: http://orcid.org/0000-0003-0721-1153 (Аналітично-порівняльне правознавство. - 2022. - № 2. - С. 349-353, 2022)
Розглянуто зв’язок юридичних міркувань, юридичної аргументації та, з іншого боку, логіки. Опрацьовано один важливий аспект зазначеного зв’язку, а саме чи є загальна, або формальна, логіка необхідною і достатньою для визначення релевантної форми юридичних міркувань та аргументації. Наголошено, що не можна стверджувати, що формальна логіка у полі права не працює зовсім. Однак сама по собі вона не детермінує релевантну форму юридичних міркувань чи аргументації, оскільки, насамперед, між формально-логічною валідністю і юридичною валідністю наявна суттєва різниця. Ця різниця ґрунтується на визнанні базової цінності права, тих чи інших особливих юридично-значущих цінностей поряд з цінністю матеріальної чи формальної істини. Відзначено, що формальна логіка не є ані достатньою, ані необхідною для того, щоб міркувати та аргументувати як юрист. Разом з тим, успішний юрист повинен засвоїти особливу юридичну логіку, що належить до домена сучасної неформальної логіки, і неухильно нею керуватися.

This article deals with general problem of connection between legal reasoning, legal argumentation and, on the other hand, logic. Although this connection seems obvious since ancient times, its nature is still the subject of non-trivial discussions. The purpose of my study is to explore one important aspect of this connection, namely, is general, or formal, logic necessary and sufficient to determine relevant form of legal reasoning and argumentation? To reach this purpose, method of comparative analysis is employed both synchronically and diachronically. First, in order to prove importance of the issue, a diachronic comparison of several basic approaches is carried out (G.W. von Leibniz, O.W. Holmes, Jr., etc.). Then a comparative analysis of the views of some contemporary experts is carried out, especially Ilmar Tammelo and Stephen Toulmin. It is argued, in the field of law there is a special legal validity that differs significantly from the formal-logical validity. The legal validity is determined directly and mainly by the value of the right not by the value of formal or material truth. It is not the subject of formal logic, but of a special legal logic and, more broadly, informal logic. Therefore, formal logic does not determine relevant form of legal reasoning and argumentation, since, first of all, there is the essential difference between the formal-logical validity and the legal validity. It is argued, formal logic is neither sufficient nor necessary to think like a jurist. In this regard, it is shown that the formal-logical standard of proof is not sufficient to determine the relevant form of valid legal proof. There are at least three standards of legal proof – proof without reasonable doubt, proof by clear and convincing evidence, and proof by preponderance of the evidence. Each of them differs significantly from the formal-logical standard. The conclusion of this research is this: it cannot be said that general logic does not work at all in the field of law. However, in order to reason and argue like a successful jurist, one must to grasp and use, without any exceptions, the special legal logic that belongs to the domain of contemporary informal logic.

Рассмотрена связь юридических рассуждений, юридической аргументации и, с другой стороны, логики. Проработан один важный аспект указанной связи, а именно есть ли общая, или формальная, логика необходимой и достаточной для определения релевантной формы юридических соображений и аргументации. Отмечено, что нельзя утверждать, что формальная логика в поле права не работает совсем. Однако сама по себе она не детерминирует релевантную форму юридических соображений или аргументации, поскольку прежде всего между формально-логической валидностью и юридической валидностью имеется существенная разница. Эта разница основывается на признании базовой ценности права, тех или иных особых юридически значимых ценностей наряду с ценностью материальной или формальной истины. Отмечено, что формальная логика не является ни достаточной, ни необходимой, чтобы рассуждать и аргументировать как юрист. Вместе с тем, успешный юрист должен усвоить особую юридическую логику, относящуюся к домену современной неформальной логики, и неуклонно ею руководствоваться.
Logic of Legal Reasoning
Тягло, О.В. Логіка юридичних міркувань [Електронний ресурс] / Тягло О. В. // Аналітично-порівняльне правознавство. - 2022. - № 2. - С. 349-353. - Режим доступу:http://app-journal.in.ua/wp-content/uploads/2022/07/67.pdf.
Keywords: Філософія. Логіка. Philosophy. Logic. Философия. Логика; Наукові публікації. Scientific publications. Научные публикации; юридичне міркування; legal reasoning; юридическое рассуждение; юридична аргументація; legal argumentation; юридическая аргументация; юридична валідність; legal validity; юридическая валидность; юридична логіка; legal logic; юридическая логика; формально-логічна валідність; formal and logical validity; формально-логическая валидность; формальна логіка; formal logic; формальная логика; неформальна логіка; informal logic; неформальная логика